2015
DOI: 10.5372/1905-7415.0905.434
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for inappropriate birth weight for gestational age

Abstract: Background:Infants with an inappropriate birth weight for their gestational age are more likely to develop complications during pregnancy and postpartum, and have increased long-term health risks. Objectives: To determine the prevalence and risk factors for infants with inappropriate birth weight for their gestational age. Methods: We enrolled 820 women with uncomplicated, singleton pregnancies who gave birth to a live born infant at term. Prepregnancy baseline and obstetric information were extracted from med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…SGA prevalence in this study was 8.8% (95%CI: 6.2% -11.9%). This finding is greater when compared with studies conducted in Thailand (31), and Brazil (32) with respective incidence rates of 2.6%, and 4.5%. Greater SGA prevalence in this study might be due to low antenatal attendance for routine check-ups and improved quality of care, as most mothers (72.0%) found in this study made less than eight antenatal visits.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…SGA prevalence in this study was 8.8% (95%CI: 6.2% -11.9%). This finding is greater when compared with studies conducted in Thailand (31), and Brazil (32) with respective incidence rates of 2.6%, and 4.5%. Greater SGA prevalence in this study might be due to low antenatal attendance for routine check-ups and improved quality of care, as most mothers (72.0%) found in this study made less than eight antenatal visits.…”
Section: Discussioncontrasting
confidence: 62%
“…In Europe, 31.0% of neonates were born small for their gestational age (30). Comparatively, the respective incidence of SGA in Thailand (31), Brazil (32), Lithuania (33), and India (34) is 2.6%, 4.5%, 10.4%, and 11.9% whilst retrospective review in Africa reported SGA prevalence of 7.2%, 14.4%, and 16.6 % in Nigeria (5), Uganda (35) and Tanzania (36) correspondingly. Alternatively, 10.5% and 15.7% of Brazilian (32) and Thai (31) women delivered LGA babies respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that maternal factors are associated with SGA. These factors include age, marital status, education, income, and parity (Ota et al, 2014); body mass index (Frederick, Williams, Sales, Martin, & Killien, 2008); gestational weight gain (Boriboonhirunsarn, 2015); preeclampsia, chronic hypertension, and anemia (Jariyapitaksakul & Tannirandorn, 2013; Ota et al, 2014); alcohol and illicit substance use (Ota et al, 2014); and psychosocial factors such as stressful life events and lack of social support (Sanguanklin et al, 2014). Fetal factors are also associated with SGA, including fetal sex, malformation, and infections (Wollmann, 2009).…”
mentioning
confidence: 99%